Sovereigns, Sterling and 'Some Bastards too!': Brexit Seen from Shakespeare's King John. (6th February 2017) - Watt, Gary
ABSTRACT: 2016 marks the 800th anniversary of the death of King John and the 400th anniversary of the death of William Shakespeare. The premise of this article is that the dynamics of human motivation which Shakespeare attributed to individuals living four hundred years before he wrote, apply as well four centuries on, in the year of "Brexit". Statistics will never tell us what led the majority of UK voters to vote "leave" on the fateful day of the EU referendum, but an appreciation of Shakespeare's King John promises to reveal something perennial about human motivations for dramatic action. It also promises to tell us a great deal about human responses, resolution and regret in the aftermath of an explosive enactment of political free will.